Development Design Labako Batik with Combine Fractal Geometry Dragon Curve and Tobacco Leaf Motif - Wulandari, Eka Yuni; Purnomo, Kosala Dwidja; Kamsyakawuni, Ahmad (Jurnal ILMU DASAR, 2017)
Labako Batik is a typical batik Jember, derived from the term "La Bako" is the language of Madura that describes the activities of farmers to plant and process the leaves of tobacco. The resulting motives are inspired by the potential of natural resources in Jember such as tobacco, cocoa, dragon fruit, coffee, bamboo, birds and butterflies. The selection of tobacco leaf pattern because Jember Regency as one of the best tobacco producing cities in Indonesia, so that the form of tobacco leaf becomes the most dominant characteristic in making Batako Labako. In recent years the application of fractal forms in batik began to be popularly known as fractal batik. Fractal batik is batik whose design is made with mathematical formulas done with computer technology. Development of Labako batik motif by generating the pattern of tobacco leaves using L-System and then combining with the fractal geometry of dragon curve that has been modeled, using techniques of geometry transformation in Matlab software. Keywords: labako batik, tobacco leaf, fractal, dragon curve, l-system